2016
DOI: 10.1016/j.schres.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Humanoid robots versus humans: How is emotional valence of facial expressions recognized by individuals with schizophrenia? An exploratory study

Abstract: Individuals do not respond similarly to human facial emotion and to non-anthropomorphic emotional signals. Humanoid robots have the potential to convey emotions to patients with schizophrenia, but their appearance seems of major importance for human-robot interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This highlights how social robots can give insight which is not accessible otherwise as ASD patients regularly avoid eye-contact with other humans but seem to gravitate socially toward therapeutic robots. Conversely, patients with schizophrenia show higher amounts of variability than neurotypicals in perceiving social robots as intentional agents (Gray et al, 2011;Raffard et al, 2018) and show distinct and complex deficits in processing facial expressions in robots (Raffard et al, 2016;Cohen et al, 2017). Application of the paradigm used here to these clinical populations may thus be valuable for identifying how behaviors and expressions associated with eye-contact in robots and in people impact processing and exacerbate or improve dysfunction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This highlights how social robots can give insight which is not accessible otherwise as ASD patients regularly avoid eye-contact with other humans but seem to gravitate socially toward therapeutic robots. Conversely, patients with schizophrenia show higher amounts of variability than neurotypicals in perceiving social robots as intentional agents (Gray et al, 2011;Raffard et al, 2018) and show distinct and complex deficits in processing facial expressions in robots (Raffard et al, 2016;Cohen et al, 2017). Application of the paradigm used here to these clinical populations may thus be valuable for identifying how behaviors and expressions associated with eye-contact in robots and in people impact processing and exacerbate or improve dysfunction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These physical pose and behavior might have affected participants' impression more than PALRO's speech. In experiments with schizophrenic patients and humanoid robots, the robot's facial expressions successfully conveyed emotions [17]. People with schizophrenia responded faster with negative facial expressions than with positive facial expressions.…”
Section: Discussionmentioning
confidence: 97%
“…To similarly support schizophrenic patients, it is necessary for robots to understand a patient's characteristics and have a trusting relationship that allows the patient to recognize a robot as a partner. A study on the relationship between schizophrenic patients and humanoid robots showed that the facial expressions of robots could convey emotions [17]. However, there are few studies on the interaction between schizophrenic patients and robots.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the lack of a facilitatory effect of social cues in schizophrenia participants may be due to specific cognitive deficits, such as an impaired ability to perceive and interpret facial social cues (i.e., smiles). In a preliminary study, we showed that patients with schizophrenia were able to accurately recognize the valence of facial emotion elicited by the same iCub robot 40 . This speaks against the concern expressed above.…”
Section: Discussionmentioning
confidence: 99%